Examining the Spatial Coordination between Metrorail Accessibility and Urban Spatial Form in the Context of Big Data - Jingming Liu (Land, 2021)
Metrorail accessibility is an important indicator that influences urban spatial form. For this article, we created a 3SFCA method to analyze the Metrorail accessibility of Shanghai covering four levels: traffic analysis zones (TAZs), stations, metrorail network, and regions. The floor area ratio (FAR) was used to reflect the urban form, and spatial coordination model was introduced to examine the spatial balance between metrorail accessibility and urban forms. Results revealed that the spatial distribution of metrorail accessibility and urban form are characterized by a monocentric spatial structure, while the values of both variables decrease gradually from urban center to suburban regions, with the regional difference being significantly greater than the other three levels. The results also indicated that the development of metrorail stations has a time lag effect on the urban spatial form, and the catchment area of a metro station shows characteristics of gradually expanding and then shrinking from city center to suburban regions. Finally, the results showed that there is a strong coordination between accessibility and urban form around metro stations, but the coordinate degree varies by regions. Thus, we concluded that station density should be increased within the fourth ring, FAR should be increased between the second and third rings, and rail transit capacity in the urban center area should be increased.